2009
DOI: 10.1523/jneurosci.3503-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

p75 and TrkA Signaling Regulates Sympathetic Neuronal Firing Patterns via Differential Modulation of Voltage-Gated Currents

Abstract: Neurotrophins such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) act through the tropomyosin-related receptor tyrosine kinases (Trk) and the pan-neurotrophin receptor (p75) to regulate complex developmental and functional properties of neurons. While NGF activates both receptor types in sympathetic neurons, differential signaling through TrkA and p75 can result in widely divergent functional outputs for neuronal survival, growth, and synaptic function. Here we show that TrkA and p75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 84 publications
(131 reference statements)
2
61
1
Order By: Relevance
“…NT-3 has an excitatory effect upon both the spontaneous and glutamate-evoked firing rates in the peripheral dendrites of auditory neurons during iontophoresis of the cochlea. While these studies and others (Lesser et al 1997;Rose et al 2004;Davis-Lopez de Carrizosa et al 2009;Luther and Birren 2009) reveal that neurotrophins can increase neuronal excitability, the effects occur extremely rapidly, within milliseconds of application, and alternate mechanisms may be required to explain the effects which emerged after several weeks of BDNF application.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…NT-3 has an excitatory effect upon both the spontaneous and glutamate-evoked firing rates in the peripheral dendrites of auditory neurons during iontophoresis of the cochlea. While these studies and others (Lesser et al 1997;Rose et al 2004;Davis-Lopez de Carrizosa et al 2009;Luther and Birren 2009) reveal that neurotrophins can increase neuronal excitability, the effects occur extremely rapidly, within milliseconds of application, and alternate mechanisms may be required to explain the effects which emerged after several weeks of BDNF application.…”
Section: Discussionmentioning
confidence: 92%
“…This is an important observation given that some other trophic effects of neurotrophins, such as the propensity to regrow or extend peripheral dendrites, are seen only in damaged areas of the organ of Corti of deafened cochleae (Wise et al 2005(Wise et al , 2010. However, the effects observed may have been anticipated given known effects of neurotrophins upon neurons; neurotrophins are known to regulate ion channel expression and to modulate firing patterns and neuronal excitability throughout the central nervous system (Holm et al 1997;Lesser et al 1997;Kafitz et al 1999;Rose et al 2004;Davis-Lopez de Carrizosa et al 2009;Luther and Birren 2009). Furthermore, it is acknowledged that the method of delivery of neurotrophins, while minimally invasive, likely caused a degree of cochlear dysfunction as evidenced by the reduction in DPOAE amplitudes, as discussed in the following paragraph.…”
Section: Discussionmentioning
confidence: 99%
“…This synaptotrophic role of neurotrophins results in changes in the balance between excitation and inhibition and in the number and activity of synapses (Singh et al, 2006;Huh et al, 2008). Moreover, neurotrophins have a role regulating discharge properties at the cellular and network levels Caleo et al, 2003;Luther and Birren, 2009). However, given the multiplicity of pathways and signaling events in the brain, combined with its heterogeneous synaptic organization, no common rule for neurotrophin action emerges that could apply to every part of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that BDNF induces tonic firing in motoneurons via TrkB receptors, whereas NT-3 induces phasic firing through TrkC receptors [104]. We postulate that retrograde influences may change the gradient of firing patterns, from tonic to phasic, as recently described for sympathetic neurons [192] by changing the synaptic weight of the afferences to motoneurons.…”
Section: A Hypothesis Linking Neurotrophic Delivery With Motoneuronalmentioning
confidence: 71%
“…Moreover, NGF has been shown to regulate excitability and firing regularity in other neuronal types through several ionic currents [191,192]. One of them is the M-current, likely present in oculomotor motoneurons, as seen with carbachol-induced depolarizations [193].…”
Section: Ngf Recovers Above Control the Discharge Activity Of Axotomimentioning
confidence: 99%